About Petrogenesis of the High aluminium Pia Oak granitoid on the base of isotopic and petrogeochemical analysis - Anh, Phan Lưu (Vietnam Journal of Earth Sciences, 2018)
High aluminium PiaOak granite formed a small intrusive, which has a simple composition...